Influence of the opposing team on the physical demands of elite Rugby League match play - Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2013)
This study investigated the influence of playing standard, and winning and losing on the physical demands of elite rugby league match play. Twenty-two elite rugby league players participated in this study. Global positioning system data were collected during 16 rugby league matches. Players covered significantly greater (p < 0.05) absolute and relative distance at high speeds when playing against Bottom 4 teams than when competing against Top 4 teams. The total distance per minute of match play and relative distance at low speeds were greater when matches were won. In addition, a greater absolute and relative number of maximal accelerations and repeated high-intensity effort bouts were performed when players were competing in winning teams than in losing teams. The mean and maximum number of efforts in a repeated high-intensity effort bout was also higher in winning teams, although the recovery between efforts was shorter in losing teams. Moderate (7-17 points) and large (>18 points) winning margins were associated with greater relative distances covered and distances covered at low speeds than small winning margins. No meaningful differences were found in the physical demands between small, moderate, and large losing margins. The results of this study demonstrate that the physical demands of rugby league are greater when winning than losing, and when competing against lower ranked teams. Furthermore, larger winning margins are associated with greater physical demands than small and moderate winning margins, with these physical demands, in turn, greater than losing margins of any magnitude. These findings suggest that the competitive advantage of successful elite rugby league teams is closely linked to their ability to maintain a higher playing intensity than their less successful counterparts.